2021
DOI: 10.1021/acs.jpclett.1c03572
|View full text |Cite
|
Sign up to set email alerts
|

Two-Step Aging of Highly Polar Glass

Abstract: Nonequilibrium processes, including physical aging, belong to the most challenging phenomena of glassy dynamics. One of the fundamental problems that needs clarification is the effect of material polarity on the time scale of the structural recovery of glass. The importance of this issue arises from practical applications and recent findings suggesting a substantial contribution of dipole–dipole interactions to the dielectric permittivity spectra of polar glass-formers. Herein, we use dielectric spectroscopy t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Another study, carried out closer to T g showed that the shape of equilibrium recovery behavior, though not showing any evident non‐monotonous pattern, was better fitted by two‐time scales. [ 30 ]…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Another study, carried out closer to T g showed that the shape of equilibrium recovery behavior, though not showing any evident non‐monotonous pattern, was better fitted by two‐time scales. [ 30 ]…”
Section: Figurementioning
confidence: 99%
“…Another study, carried out closer to T g showed that the shape of equilibrium recovery behavior, though not showing any evident non-monotonous pattern, was better fitted by two-time scales. [30] The presence of multiple steps of equilibrium recovery underlines the presence of different mechanisms of equilibration. While, as previously explained, highlighting their simultaneous presence is a hard task in isothermal aging, isochronal measurements, for instance heating at a constant rate after aging way below T g , helps to unveil the existence of the fast mechanism of equilibration, that is, the one relevant for the first decay in isothermal experiments.…”
mentioning
confidence: 99%
“…In various industries such as construction, daily use, and healthcare, glass, as a direct interface between people and the environment, people and machinery, the development of glass materials and their performance has garnered more and more attention from both consumers and professionals [1][2][3]. In glass applications, glass is inevitably affected by factors such as temperature, humidity, and ultraviolet radiation, which can lead to a reduction in the mechanical properties and service life of the glass [4][5]. Therefore, studying the ultraviolet radiation performance of glass in comparison to normal environmental conditions is of paramount importance.…”
Section: Introductionmentioning
confidence: 99%
“…It should be highlighted that, up to now, the vast majority of such annealing experiments were performed only in a limited range of temperatures ( T < T g,interfacial ), as above T g,interfacial , the effects of isothermal time-dependent measurements were hardly detectable. It is also worth mentioning that S -methoxy-PC (static permittivity, ε s ∼180) , was explicitly chosen due to strong dipole–dipole interactions and interesting effects (i.e., two-step aging) accompanying equilibration of this compound below T g . …”
mentioning
confidence: 99%
“…It is also worth mentioning that S -methoxy-PC (static permittivity, ε s ∼180) 24 , 25 was explicitly chosen due to strong dipole–dipole interactions and interesting effects (i.e., two-step aging) accompanying equilibration of this compound below T g . 26 28 …”
mentioning
confidence: 99%